Metabolomics of rapeseed (Brassica napus var. oleifera Del.) sprouts obtained with or without salinity from progeny seeds of mother plants grown in presence or absence of salinity - F. Sevi; B. Falcinelli; S. Frusciante; E. Fabene; G. Tosti; R. D'Amato; G. Diretto; P. Benincasa (Journal of Agriculture and Food Research)
This work aimed at evaluating changes in the whole non volatile metabolome of rapeseed sprouts caused by imposing salt stress during the growth of mother plants where offspring seeds used for sprouting where taken from, or during the sprouting of offspring seeds, or during both phases. To this purpose, seeds harvested from mother plants grown with or without salinity (100 and 0 mM NaCl, respectively) were sprouted with or without salinity (50 and 0 mM NaCl) to obtain four treatments: 100-0, aimed at evaluating the intergenerational effect of stress applied to mother plants (i.e., stress memory); 0–50, aimed at evaluating the consequences of stress applied during sprouting (i.e., current stress); 100-50, aimed at evaluating the effect of combined salt stress (stress memory + current stress); 0-0, as a never stressed control. Overall, either the stress memory (100-0) or the current stress (0–50) boosted the concentrations of several phenolic compounds, fatty acids, cis-9-monoolein, while 100-0 also showed increased contents of spermidine, riboflavin, and chlorophyll a. Combining the two stress occurrences (i.e.,100-50) further triggered the over-accumulation of amino acids, organic acids, vitamins, carotenoids, chlorophylls and phylloquinone, as compared to 100-0 and 0–50 but, conversely, more phenolic compounds resulted down-regulated.